2019
DOI: 10.3171/2019.3.spine18993
|View full text |Cite
|
Sign up to set email alerts
|

Decision tree analysis to better control treatment effects in spinal cord injury clinical research

Abstract: OBJECTIVEThe aim of this study was to use decision tree modeling to identify optimal stratification groups considering both the neurological impairment and spinal column injury and to investigate the change in motor score as an example of a practical application. Inherent heterogeneity in spinal cord injury (SCI) introduces variation in natural recovery, compromising the ability to identify true treatment effects in clinical research. Optimized stratification factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…We also graphically examined the association between the SCIRS and ISS (see Supplementary Figure S5). Results showed a positive correlation between the SCIRS and ISS scores (Pearson's correlation = 0.30, p<0.05) which supported the validity of the SCIRS given that ISS is a well-known index that has previously been used in tSCI research [11,[35][36][37]. This figure also demonstrates that the SCIRS is more sensitive than ISS in measuring mortality in the datasets.…”
Section: Validation Of Scirssupporting
confidence: 67%
“…We also graphically examined the association between the SCIRS and ISS (see Supplementary Figure S5). Results showed a positive correlation between the SCIRS and ISS scores (Pearson's correlation = 0.30, p<0.05) which supported the validity of the SCIRS given that ISS is a well-known index that has previously been used in tSCI research [11,[35][36][37]. This figure also demonstrates that the SCIRS is more sensitive than ISS in measuring mortality in the datasets.…”
Section: Validation Of Scirssupporting
confidence: 67%
“…57,93 There is stronger literature for age >50 being associated with poorer outcomes. 61,92,[95][96][97][98][99][100][101][102] Oleson and associates 92 (in patients with AIS B grade) and Penrod and colleagues 97 (in patients with motor incomplete injuries) found that, overall, patients age >50 years had a decreased likelihood of recovering walking ability one year post-injury, relative to patients under age 50. Burns and associates 98 reported an increased likelihood of achieving community ambulation in patients with incomplete tetraplegia and paraplegia on discharge from rehabilitation in individuals with AIS C who were <50 (91%) compared with those ‡50 years of age (42%), although for individuals presenting with an initial AIS D, age was not a factor in ambulation because all were able to ambulate 3-6 months post-injury.…”
Section: Age and Impact On Neurological Recoverymentioning
confidence: 99%
“…Finally, the branch containing AOSpine A and B injuries in the cervical spine were passed through another internal node for "age, " generating another three leaves or clusters. The final six clusters are detailed in Table 4 (32). The results of this study provide a platform for external validation studies with other patient cohorts to compare this unique classification system with current ones.…”
Section: Decision Tree Learningmentioning
confidence: 94%
“…Tee et al application of decision tree learning for optimizing patient risk stratification after spinal cord injury provides a framework for understanding this modality (32). They combined different methods of assessing spinal cord function after trauma, including the American Spinal Injury Association (ASIA) Impairment Scale, total motor score (TMS) and the AOSpine classification system, to allow a decision tree to identify patient clusters that respond differently to treatment.…”
Section: Decision Tree Learningmentioning
confidence: 99%
See 1 more Smart Citation